Sudden Stops and Asset Purchase Programmes in the Euro Area - Josefina Fabiani; Michael Fidora; Ralph Setzer; Andreas Westphal; Nico Zorell (Credit and Capital Markets – Kredit und Kapital, 2021)
This paper analyses the incidence and severity of sudden stops in euro area countries before and after the introduction of the ECB's asset purchase programmes. We define sudden stops as abrupt declines in private net financial inflows, i.e. total flows adjusted for EU and IMF loans and changes in TARGET2 balances. We document that sudden stop were more frequent and more severe in euro area countries compared to other OECD economies over the period 1999–2020. We find that the susceptibility of euro area countries to severe sudden stops mainly reflects domestic fundamentals whereas there is no clear evidence of an adverse direct effect of being part of the euro area. Moreover, our econometric analysis suggests that the ECB asset purchase programmes have overall almost halved the risk of severe sudden stops in euro area countries. We find tentative evidence that this effect operates through confidence channels.
Keywords: F21; F31; F32; F41; F45; 330; Financial flows; sudden stops; monetary policy; ECB asset purchase programmes